The potential antidiabetic properties of purple tea [Camellia sinensis (L.) O Kuntze], purple tea ellagitannins, and urolithins - Zeno, Apostolides (University of Pretoria, 2023)
Thesis (PhD (Biochemistry))--University of Pretoria, 2023.